Image processing based object tracking application with fractional-order model reference controller - Kavuran, Gurkan; Ates, Abdullah; Alagoz, B. Baykant; Yeroglu, Celaleddin (Pamukkale Univ, 2016)
In this paper, position control application of DC servo motor is investigated by using conventional model reference adaptive control structure with fractional order integrator. Modification of the controller is achieved by fractional order integrator in adaptation rule. Object position for reference input of control system is updated in real time by the values obtained from camera of object tracking system. Results obtained for integer order integrator and fractionalorder integrator for model reference adaptive control system are compared and it is observed that the fractional-order integrator can provide faster adaptation for the system.
Keywords: Fractional order calculus; Model reference adaptive control; Object tracking; Servomotors